As múltiplas dimensões do cuidado de si e dos outros no trabalho das Agentes Comunitárias de Saúde em contextos de vulnerabilidade social e de enfrentamento da COVID-19 - Silva, Mônica Jesus da (2022)
This research aimed to understand the multiple dimensions of caring for oneself and for others in the work of Community Health Agents in contexts of social vulnerability and coping with Covid-19. The theoretical framework is anchored in the constructionist approach and based on the dialogical ethics discussed by Mary Jane Spink et al. (2014), who consider the implications of scientific production in people's lives. For data collection, four conversation circles were carried out, favoring an atmosphere of spontaneous conversation among the participants and the expression of ideas and affections. To analyze the dialogue that took place in the circles, firstly, the sequential transcription of the recordings was used to identify the main topics covered, then used to build the dialogic maps to carry out a detailed analysis and respond to the specific objectives of this research. The first map was about “Facing the pandemic” with the categories: (1) Experiences of the pandemic; (2) “I”; (3) The family; (4) The work of ACS during the pandemic; (5) Impacts of the pandemic on the territory and on the relationship with patients; (6) The work of ACS in Basic Health Units. To understand the multiple dimensions of caring for oneself and others in the work of ACS, we used analysis of narratives about: (a) Caring for others: reports about patients; (b) Caring for others: reports about the family; (c) Take care of yourself. As a result, the moving reports about the pandemic and its consequences in the daily work of the ACS allowed feelings of personal and professional devaluation to emerge; interpersonal conflicts and physical and emotional exhaustion. Being ACS and being a woman is to be crossed by gender and care issues as a feminine attribute, which often make them feel overwhelmed, afraid and uncertain about their own future